Ocular vestibular evoked myogenic potential elicited from binaural air-conducted stimulations: clinical feasibility in patients with peripheral vestibular dysfunction. (July 2013) - Iwasaki, Shinichi; Egami, Naoya; Inoue, Aki; Kinoshita, Makoto; Fujimoto, Chisato; Murofushi, Toshihisa; Yamasoba, Tatsuya
Abstract Conclusion: Ocular vestibular evoked myogenic potentials (oVEMPs) to binaural air-conducted stimulation (ACS) may provide a convenient way of assessing the crossed vestibulo-ocular reflex in patients with vestibular dysfunction as well as in healthy subjects. Objective: To investigate the clinical feasibility of using oVEMPs in response to binaural ACS to assess normal subjects and patients with vestibular dysfunction. Methods: The study investigated 24 normal subjects (14 men and 10 women, aged from 23 to 60 years) and 14 patients with unilateral peripheral vestibular dysfunction. Each subject underwent oVEMP testing in response to monaural ACS and binaural ACS (500 Hz tone burst, 135 dBSPL). Results: In normal subjects, bilateral oVEMPs were elicited in 75% of subjects in response to monaural ACS and in 91% in response to binaural ACS. Asymmetry ratios (ARs) of the responses to binaural ACS were significantly smaller than those of the responses to monaural ACS (p < 0.01). In patients with unilateral vestibular dysfunction, there were no significant differences in the amplitude, latency, or AR of the responses between monaural and binaural ACS. Approximately 30% of patients showed reduced ARs to binaural ACS relative to monaural ACS, primarily due to contamination by uncrossed responses elicited in healthy ears.